Cultura e turismo na contemporaneidade: as festas populares religiosas baianas - Sá, Natalia Silva Coimbra de (2007)
This dissertation analyzes the way that culture is used to elaborate and promote Bahia touristy product and the role that the religious popular festivals play in this process. The analysis is made through the study of two official documents published in 2005 by the Sectretaria da Cultura e Turismo SCT, the main official institution for culture and tourism in the state of Bahia between 1991 and 2006. One of the documents is dedicated to the cultural public policies and the other to the tourism public policies. From the universal point of view, the analysis is made based on the context of globalization, new territorialities and post-modernism. At the same time it is highlighted the role that the cultural process and the touristy phenomenon play in the contemporary societies both in the national and global level, and their importance as social, cultural and economic activities. At the same time, it is presented and discussed some of the main concepts that the cultural motivated tourism´ speech uses with the contribution of the Cultural Studies. In the particular aspects, it is analyzed some of the theories about festivals and the way that they are related to the popular, sacred and secular issues. The singular aspect of the analysis, that is the main object of this dissertation, is related to the religious popular festivals in Bahia and how those, along with the syncretism (which is one of its constitution elements), have such importance to the baianidade speech, one of the most powerful tools of touristy planning and marketing in the state. What this dissertation tries to demonstrate is that the religious popular festivals in Bahia, besides the fact that they are an important touristy product are also an important constitutive element of a powerful symbolic construct that sets the base to the official tourism strategies.